Innovation Centers in Health Care Delivery Systems: Structures for Success - Onil Bhattacharyya; Justin Shapiro; Eric C Schneider (JMIR Publications, 2022)
The need to support innovation in health care delivery was prompted by payment reforms and access to digital tools and has been accelerated by the shift to virtual care as part of the COVID-19 pandemic response. Prior to the pandemic, a growing number of health systems set up innovation centers to focus on creating new services and exploring new business models relevant to value-based care. This is distinct from process improvement or implementation science, and often needs a different set of incentives to succeed within a large organization. We used a national survey to identify a diverse sample of innovation centers, and interviewed leaders to describe their aims, organizational structures, and activities. They all aim to improve patient outcomes and experience while reducing costs, but their strategic focus may differ. The centers also vary in their reporting structure, how they build internal capacity, and how they measure success. We highlight the range of strategies through examples of projects that improve quality, reduce costs, and generate new revenue. While the optimal forms and impact of innovation centers are still emerging, the fiscal pressures and the rapid uptake of digital technologies present opportunities for the redesign of health services in the postpandemic era. The experiences of these centers illustrate a set of approaches to increase any organization's capacity for innovation.